Corrosion inhibition of pure aluminium and AA2014‐T6 alloy by strontium chromate at low concentration. (18th November 2015) - Liu, Yanwen; Feng, Zuwei; Zhou, Xiaorong; Thompson, George E.; Skeldon, Peter; Lyon, Stuart B.; Gibbon, Simon R.; Graham, Derek
Abstract : The influence of a low concentration of strontium chromate on the corrosion inhibition of superpure aluminium and AA2014‐T6 aluminium alloy in 0.6 m chloride solution has been investigated to simulate the leaching process of inhibitors from coatings. The potential‐time and polarisation behaviour show influences on both the anodic and cathodic kinetics on the superpure aluminium surface. However, predominant cathodic inhibition was observed for the AA2014‐T6 aluminium alloy. It was evident that chromium species were reduced at cathodic second phase particles, forming a thin passive film at the cathodic sites, which blocks the oxygen reduction reaction and, consequently, provides effective corrosion inhibition. Copyright © 2015 The Authors Surface and Interface Analysis Published by John Wiley & Sons Ltd.